Fatal misuse of transdermal fentanyl patches. (September 2019) - Geile, J.; Maas, A.; Kraemer, M.; Doberentz, E.; Madea, B.
Highlights: Fatal fentanyl patch misuse is rare compared to illicit fentanyl abuse. Co-administered drugs are frequently found in cases of fentanyl patch misuse. Mixed drug intoxications are more frequent than fentanyl intoxications. Interpretation of fentanyl concentrations should include detection of norfentanyl. Hair analysis may aid in identifying opioid-tolerant individuals. Abstract: Fentanyl is a potent synthetic opioid with a variety of possible applications. Transdermal fentanyl patches are regularly prescribed for patients with severe chronic or cancer-related pain. The potential for abuse is well-known and cases associated with illicit fentanyl intake are common. Fentanyl related fatalities due to unintentional misuse are relatively rare. This study focused on those instances and their identification in forensic examinations and adds new cases and consolidates the existing femoral blood concentrations in the event of fatal fentanyl patch misapplications. A total of 35 cases between 2010 and 2018 in which transdermal fentanyl patches were detected during forensic autopsies were identified and reviewed for the frequency of unspecific macroscopic signs of opioid intoxication. Furthermore, a detailed examination is presented for 11 cases in which toxicological results were available. The cause of death was eventually considered to be related to fentanyl patch misuse in 5 of these 11 cases. Co-administered drugs and signs of opioid intoxication, especially pulmonary edema, were frequently found. Lastly, it is advised to include norfentanyl and hair analysis in the interpretation of post-mortem fentanyl concentrations.